glh-1, a germ-line putative RNA helicase from Caenorhabditis, has four zinc fingers. - Roussell, D L (1993)
We have cloned a family of putative RNA helicases from the free-living nematode Caenorhabditis elegans. One of these, a cDNA that we call glh-1, most closely matches in sequence and expression the previously described germ-line helicases PL10 from mouse and vasa from Drosophila. The amino terminus of the predicted protein of glh-1 contains a set of glycine-rich repeats similar in location and sequence to those in the predicted vasa protein. However, unlike all other putative RNA helicases, glh-1 also contains four retroviral-type zinc fingers. The RNA expression pattern of this Caenorhabditis helicase correlates with the presence of germ-line tissue in the parasitic nematode Ascaris lumbricoides var. suum and with the presence of germ cells in wild type and several germ-line mutants of Caenorhabditis. In the germ-line mutants glp-4 and glp-1, additional larger species of glh-1 RNA exist, which correspond to different adenylylated forms of the glh-1 transcript; these may be specified by motifs in the 3' untranslated region of glh-1 that are similar to adenylylation control elements and nos response elements.